The Kalash genetic isolate: ancient divergence, drift, and selection. - Ayub, Qasim; Mezzavilla, Massimo; Pagani, Luca; Haber, Marc; Mohyuddin, Aisha; Khaliq, Shagufta; Mehdi, Syed Qasim; Tyler-Smith, Chris (Am J Hum Genet, 2015)
The Kalash represent an enigmatic isolated population of Indo-European speakers who have been living for centuries in the Hindu Kush mountain ranges of present-day Pakistan. Previous Y chromosome and mitochondrial DNA markers provided no support for their claimed Greek descent following Alexander III of Macedon's invasion of this region, and analysis of autosomal loci provided evidence of a strong genetic bottleneck. To understand their origins and demography further, we genotyped 23 unrelated Kalash samples on the Illumina HumanOmni2.5M-8 BeadChip and sequenced one male individual at high coverage on an Illumina HiSeq 2000. Comparison with published data from ancient hunter-gatherers and European farmers showed that the Kalash share genetic drift with the Paleolithic Siberian hunter-gatherers and might represent an extremely drifted ancient northern Eurasian population that also contributed to European and Near Eastern ancestry. Since the split from other South Asian populations, the Kalash have maintained a low long-term effective population size (2,319-2,603) and experienced no detectable gene flow from their geographic neighbors in Pakistan or from other extant Eurasian populations. The mean time of divergence between the Kalash and other populations currently residing in this region was estimated to be 11,800 (95% confidence interval = 10,600-12,600) years ago, and thus they represent present-day descendants of some of the earliest migrants into the Indian sub-continent from West Asia.
Keywords: Asia; Asian Continental Ancestry Group; Chromosomes, Human, Y; Demography; DNA, Mitochondrial; European Continental Ancestry Group; Genetic Drift; Genetics, Population; Haplotypes; History, Ancient; Humans; Male; Pakistan; Phylogeny